DEVELOPMENT OF RS-WZ3 SENSOR IN IOT BASED VIBRATION MONITORING SYSTEM - Indrasari, Widyaningrum; Hermanta, Catur Anthony; Firmansyah, Heri (Jurnal Neutrino:Jurnal Fisika dan Aplikasinya, 2024)
This article develops a vibration monitoring system on the machine using the RS-WZ3 sensor, which is based on MEMS (Micro-Electro-Mechanical Systems) technology. The RS-WZ3 sensor can measure vibrations on three axes (X, Y, and Z), as well as the surface temperature of the motor. The MAX485 module and the ESP32 microcontroller transform the vibration data from the sensor into a digital signal, subsequently displaying it on a web interface accessible remotely in real time. Sensor calibration is carried out by comparing the measurement results of the RS-WZ3 sensor with those of the GM63A vibration meter, which shows good accuracy with an average error of 2.01%. Testing of this system shows that the RS-WZ3 sensor is effective in measuring and monitoring machine vibrations in real time, enabling more efficient predictive maintenance and reducing maintenance costs.